2021
DOI: 10.1371/journal.pmed.1003652
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of risk of prolonged post-concussion symptoms: Derivation and validation of the TRICORDRR (Toronto Rehabilitation Institute Concussion Outcome Determination and Rehab Recommendations) score

Abstract: Background Approximately 10% to 20% of people with concussion experience prolonged post-concussion symptoms (PPCS). There is limited information identifying risk factors for PPCS in adult populations. This study aimed to derive a risk score for PPCS by determining which demographic factors, premorbid health conditions, and healthcare utilization patterns are associated with need for prolonged concussion care among a large cohort of adults with concussion. Methods and findings Data from a cohort study (Ontari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
33
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(36 citation statements)
references
References 35 publications
(48 reference statements)
2
33
1
Order By: Relevance
“…A minority of patients, about 15–20%, recover slowly or not at all [ 3 , 4 , 5 ]. Almost all of these have depressive or anxiety symptoms [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…A minority of patients, about 15–20%, recover slowly or not at all [ 3 , 4 , 5 ]. Almost all of these have depressive or anxiety symptoms [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similar to concussed patients, systemic inflammation seems to be associated with psychological conditions such as depression, anxiety, and post-traumatic stress disorder (PTSD) in the non-concussed population [ 28 , 29 , 30 ]. This led us to question whether the same inflammatory mediators were active in concussed patients and played a role in the genesis of post-concussion emotional impairments, particularly depression, anxiety, and PTSD, that are hallmarks of persistent post-concussion symptoms (PPCS) [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…46 Moreover, in a study of adults with concussions seen by a primary care physician or emergency department, premorbid psychiatric conditions (eg, depression and anxiety) were a predictor of longer recovery, along with older age, comorbid personality disorders, and preinjury health care utilization. 27 Similarly, pediatric patients, aged 12 to 18 years, with preexisting emotional distress (eg, depression and anxiety) exhibited longer symptom resolution relative to patients without a history of depression or anxiety. 39 Importantly, the authors also reported that girls and women experienced longer recovery times as well as higher percentages of preexisting anxiety compared with men.…”
Section: Discussionmentioning
confidence: 98%
“…Studies report that more than half of people with PCS still have symptoms more than 1 year after the injury. 10,11 PCS usually disappears within 2-4 weeks but some studies have found PCS last more than 6 months (latent onset). Another study states that PCS may be permanent if recovery has not occurred within 3 years.…”
Section: Bioscientia Medicina: Journal Of Biomedicine and Translation...mentioning
confidence: 99%